LEGAL ANALYSIS OF LATE MARRIAGE REGISTRATION APPROVAL AT TANJUNGPINANG DISTRICT COURT (Case Study of Decision 24/Pdt.P/2023/PN Tpg) - Irma Prawita Saragih; Lily Washliati; Markus Gunawan (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2025)
Marriage is a legal act that has legal consequences for both husband and wife and for the status of children. Marriage registration, as regulated in Law Number 1 of 1974 concerning Marriage in conjunction with Law Number 16 of 2019 and Law Number 23 of 2006 concerning Population Administration in conjunction with Law Number 24 of 2013, is crucial to ensure legal certainty and protection. However, in practice, some marriages are not promptly registered, leading to legal issues, one of which is the case of late marriage registration validation, as decided in Decision Number 24/Pdt.P/2023/PN Tpg at the Tanjungpinang District Court. The purpose of this study is to determine and analyze the judge's legal considerations in granting requests for late marriage registration validation, examine the legal consequences of these decisions on marital status and the status of children, and identify obstacles and solutions to implementing late marriage registration validation. This study employed a normative-empirical legal research method with statutory, case-based, conceptual, and sociological-empirical approaches. Data were obtained from legislation, doctrine, court decisions, and interviews, then analyzed qualitatively to assess the consistency of the application of legal norms in judicial practice. The results show that the Panel of Judges, in Decision Number 24/Pdt.P/2023/PN Tpg, granted the applicant's petition, considering the fulfillment of formal and material requirements according to civil procedural law, and for the sake of legal certainty. The decision affirmed that a valid marriage according to religion can still obtain formal legality through late registration with court permission. In conclusion, the validation of late marriage registration provides legal protection for the legal status of husband, wife, and children. The author recommends that the public be more disciplined in registering marriages from the outset, and that the government improve public awareness and marriage administration services to prevent similar cases in the future.